The Effect of [Glu][H2PO4] via Foliar Spraying on Cadmium and Arsenic Absorption and Translocation in Rice Plants - Jiawei Deng; Lin Fu; Yanan Wang; Changbo Zhang; Yun Deng; Xin Luo; Gilles Mailhot (Toxics)
Rice is the main source of cadmium (Cd) and arsenic (As) in Chinese diet. The formulation of targeted agronomic interventions for mitigating Cd and As bioaccumulation in rice grains constitutes a critical pathway toward ensuring food safety and public health security. Foliar spraying technology with ionic liquids, effectively reduces Cd/As content in rice. In this study, an ionic liquid of amino acids ([Glu][H2PO4]) as a foliar conditioner was applied to two varieties of rice (X24 and Z35) to explore the mechanism of reducing the accumulation of Cd/As in rice. The results showed that [Glu][H2PO4] reduced Cd/As levels by up to 58.57% and 44.09%, respectively. [Glu][H2PO4] reduced the transfer factor from the root system to flag leaves, nodes, and other organs, thus reducing the Cd/As content in them. [Glu][H2PO4] promoted amino acid synthesis in seeds, increased Ca2+ level, increased OsGLR3.1–3.5 expression, and decreased OsLsi1–3 expression in flag leaves, thereby Cd/As was inhibited from being absorbed and transported by rice. The results demonstrated that the foliar application of [Glu][H2PO4] significantly mitigated the accumulation of Cd/As in rice. This study introduces a novel and effective strategy for reducing Cd/As accumulation in rice, hoping to enhance the safety and quality of rice crops.